SunRISE Ground Radio Lab: Monitoring Solar Radio Bursts With an Expansive Array of Antennae at High Schools Nationwide - M. Akhavan‐Tafti; S. L. Soni; C. Higgins; S. Fung; S. Lepri; J. Lux; J. Lazio; A. Romero‐Wolf (Earth and Space Science, 2025)
Abstract The Sun Radio Interferometer Space Experiment (SunRISE) Ground Radio Lab (GRL) is a Science, Technology, Engineering, Arts, and Mathematics (STEAM) project, sponsored by NASA's SunRISE mission and organized by the University of Michigan College of Engineering. The project aims to engage and train the next generations of scholars. To achieve this, the project deployed antennas to 18 high schools nationwide to observe solar radio bursts (SRB). SRBs are defined as low‐frequency radio emissions emanated by accelerated electrons associated with extreme solar activity, including solar flares and coronal mass ejections (CMEs). Type II SRBs were found to predominantly correspond to coronal shocks caused by CMEs, highlighting particle acceleration events in the solar atmosphere and interplanetary space. These bursts can act as early warning signs of upcoming solar disturbances which can lead to geomagnetic storms. The type II bursts were then investigated to estimate the corresponding shock and Alfvén speeds: 277 < vshock < 1,480 km/s and 194 < vA < 947 km/s at heliocentric distances of around 1–2 solar radii, respectively. The Alfvén Mach number was further found to be 1.2 < MA < 2, while the measured magnetic field strength followed a single power law of B(r) = 0.3 r−2, where r represents the heliocentric distance. Our results were found to agree with previous studies. Through SunRISE GRL, an ever‐expanding catalog of SRBs is being collected by high school students nationwide, curated by a team of solar physics experts, and made publicly available to the scientific community to make progress toward the SunRISE mission's objectives.